The association of adiposity rebound age and cognitive function in early adulthood - Järvinen, Alina (My University, 2024)
The prevalence of obesity is increasing worldwide among both adults and children. Obesity is a well-known risk factor for several diseases, including metabolic syndrome, type 2 diabetes and certain cancers. During childhood BMI increases twice: there is a strong increase in BMI during the first year of life, which is followed by a slow decrease in BMI during the next few years. The second increase in BMI occurs at around the age of 3-8 years, and this increase is called the adiposity rebound. According to previous studies, early adiposity rebound age is associated with obesity in later life, and obesity has in some studies been associated with lower cognitive function compared to normal weight. The purpose of this study was to find whether there is an association between adiposity rebound age and cognitive function in later life. The analyses are based on the randomised controlled Special Turku Coronary Risk Factor Intervention Project (STRIP). The height and weight of the participants were measured annually, and the adiposity rebound age was defined for each child. Cognitive function was measured at age 26 years using Cambridge Neuropsychological Test Automated Battery (CANTAB). We found an association between adiposity rebound at older age and better cognitive function in girls, specifically better cognitive flexibility. Adiposity rebound age explained 4.7 % of the variation in cognitive flexibility, while adiposity rebound age combined with socioeconomic status and adult BMI explained as much as 10 % of this variation. Our results indicate that early adiposity rebound might link with slightly poorer performance in this particular cognitive domain.
Keywords: adiposity rebound age, cognitive function, obesity